(untitled) (Raparin Journal of Humanities (RJH), 2019)
Laurie Halse Anderson’s Speak (1999) is her first landmark work addressing a social problem—rape—that is all too common to girls entering adolescence in the United States. This paper employs a feminist approach that presents the painful narrative of the rape victim and investigates the novel’s promotion of individual, resistant action within the oppressive social structure, achieved through what the postmodernist feminist Judith Butler calls “gender performativity”. It is this individual agency or subjectivity that enables the protagonist in Speak to overcome the adverse effects of rape, which is the product of a patriarchal system that regards females the second sex, to borrow the term by the French, feminist thinker Simone de Beauvoir. As such, Speak functions as a site of discursive resistance against such a patriarchal system by resisting some of the popularly held myths that discredit rape victims’ narratives.